Prevalence of suicidal behavior in patients with chronic pain: a systematic review and meta-analysis of observational studies - Kwon, Chan-Young; Lee, Boram (Frontiers in Psychology, 2023)
Objective Chronic pain is a leading cause of disability, severely impairing an individual’s daily activity and quality of life. In addition, this condition may contribute to suicidal thoughts by leading to neuropsychological impairments, a perceived lack of meaning in life, and pain-related catastrophizing. This systematic review aimed to comprehensively investigate the prevalence and associated factors of suicidal behaviors (SBs) including suicidal ideation (SI) and suicide attempt (SA) or its complete, in individuals with chronic pain. Methods Five electronic databases were searched up to October 4, 2022. Only observational studies investigating the prevalence of SB in individuals with chronic pain were included. The methodological quality of the included studies was assessed using the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) statement. A meta-analysis was conducted to quantify the prevalence of SB in the population, and the command “Metaprop” was used in STATA/MP 16. In addition, factors explaining the association between chronic pain and SB identified through regression analysis were investigated. Results A total of 19 studies were included in this review (N = 3,312,343). The pooled lifetime prevalence of SI and SA was 28.90% (95% confidence interval, 17.95 to 41.26%) and 10.83% (5.72 to 17.30%), respectively, in a mixed sample comprising various chronic pain conditions. Importantly, the pooled prevalence of past 2-week SI was as high as 25.87% (18.09 to 34.50%). The methodological quality of the included studies was not optimal, and studies using validated SB assessment tools were lacking. Potential protective factors against SB in this population included pain coping and self-efficacy, older age, certain race/ethnicity groups, and marriage. Conclusion This systematic review and meta-analysis demonstrated the high prevalence of SB in individuals with chronic pain. Specifically, around 1 in 4 individuals with chronic pain had SI within the last 2 weeks. However, there was considerable heterogeneity in the pooled prevalence of SB in this population.